(untitled) (Advancements in Homeopathic Research, 2023)
Urticaria is a vascular reaction of the superficial portion of the dermis. It is characterized by appearance of erythematous, oedematous papules or plaques known as wheals. The present article is a case report of a 17-year-old male visited to the OPD of Swasthya Kalyan Homoeopathic Medical College and Research Centre with the complaint of eruptions (wheals) on left forearm. After complete case taking and thorough analysis and repertorization using synthesis repertory, Phosphorus 30C was selected and prescribed based on individualization. This article illustrates the beneficial effects of Homoeopathic medicine Phosphorus in the case of Urticaria.